2021
DOI: 10.1128/msystems.01068-21
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Multiplex Tiling PCR Sequencing Approaches for Detecting Genomic Variants of SARS-CoV-2 in Municipal Wastewater

Abstract: Monitoring the genomic characteristics of the SARS-CoV-2 virus circulating in a population can shed important insights into epidemiological aspects of the COVID-19 outbreak. Sequencing every clinical patient sample in a highly populous area is a difficult feat, and thus sequencing SARS-CoV-2 RNA in municipal wastewater offers great promise to augment genomic surveillance by characterizing a pooled population sample matrix, particularly during an escalating outbreak.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 24 publications
2
35
0
Order By: Relevance
“…These methods were developed for clinical use but have been applied for the analysis of wastewater samples. These include tiled amplicon approaches such as a Nanopore-based method utilizing 89 primer sets ( Izquierdo-Lara et al, 2021 ; Oude Munnink et al, 2020 ), or ones that employ ARTIC primer sets ( Lin et al, 2021 ; Nemudryi et al, 2020 ; Rios et al, 2021 ; Swift et al, 2021 ). Other tiling amplicon approaches include ATOPlex, utilizing 259 primer sets ( Ni et al, 2021 ), or Illumina sequencing with the Swift Nomalase® Amplicon SARS CoV-2 Panel (SNAP) panel ( Fontenele et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These methods were developed for clinical use but have been applied for the analysis of wastewater samples. These include tiled amplicon approaches such as a Nanopore-based method utilizing 89 primer sets ( Izquierdo-Lara et al, 2021 ; Oude Munnink et al, 2020 ), or ones that employ ARTIC primer sets ( Lin et al, 2021 ; Nemudryi et al, 2020 ; Rios et al, 2021 ; Swift et al, 2021 ). Other tiling amplicon approaches include ATOPlex, utilizing 259 primer sets ( Ni et al, 2021 ), or Illumina sequencing with the Swift Nomalase® Amplicon SARS CoV-2 Panel (SNAP) panel ( Fontenele et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the sensitivity of multiplex tiling PCR assays may be dependent on aspects of the primer panel design, such as amplicon length. Such effects were systematically explored by Lin et al (2021) by conducting a comparison of three different multiplex tiling PCR primer sets of different amplicon length (150 bp, 400 bp, 1200 bp) with the same wastewater samples with Cq values ranging from 29 to 36, which revealed that shorter amplicons (e.g. 150 bp Swift Biosciences) were less succeptible to decreasing detection rates at lower viral concentrations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This bioanalytical approach was applied to IWW samples from different locations in Belgium to retrospectively monitor the emergence of each VOC at a population scale. To our knowledge, most pre-existing WBE applications on SARS-CoV-2 variants mainly focus on sequencing [ 29 , 34 , 35 , 36 , 37 ] and RT-qPCR [ 26 , 28 , 38 , 39 ]. Only a limited number of studies have applied dPCR to estimate the VOC circulation in IWW [ 25 , 27 , 40 , 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…As soon as viral genomes of VOCs become available within the international scientific community, e.g., via GISAID (Elbe & Buckland-Merrett, 2017), variant-specific PCR primers and probes can be developed and deployed on regularly collected wastewater samples to understand the dynamics of community disease burden caused by VOCs (Peterson et al 2022). While sequencing viral genomes from wastewater is technically feasible, either via targeted amplicon tiling protocols (Rios et al 2021; Lin et al 2021) or shotgun metagenomics (Rothman et al 2021; Pérez-Cataluña et al 2022), these comprehensive approaches are significantly more costly and time consuming than targeted RT-qPCR screening of RNA extracted from wastewater that can provide accurate data on VOCs at a fraction of the cost, and in near-real time. In Alberta wastewater is sampled, processed and analyzed in university laboratories in Calgary and Edmonton, and reported to health officials and online to the public two days after sampling.…”
Section: Introductionmentioning
confidence: 99%